2007
DOI: 10.1002/dc.20640
|View full text |Cite
|
Sign up to set email alerts
|

Automated screening versus manual screening: A comparison of the ThinPrep® imaging system and manual screening in a time study

Abstract: The ThinPrep Imaging System (TIS) is an automated system that assists cytotechnologists in the primary screening of ThinPrep liquid based cervical samples. Between June 1, 2004, and April 1, 2005, four experienced cytotechnologists participated in the study in which the duration of the screening procedure was timed for each of the 11,354 slides included. In every slide 22 fields of view were reviewed, and the samples that contained potentially abnormal cells were fully screened. The screening time was reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 11 publications
3
50
1
Order By: Relevance
“…14 Studies published since, which have evaluated the cost and productivity implications associated with using the ThinPrep Imaging System and BD FocalPoint GS Imaging system, have suggested that automation results in both increased productivity and increased costs. In all studies the authors found that automation resulted in at least a 50% 25,26,29 increase in productivity, with the biggest increase reported being 56%. 32 A study based in Italy which estimated the costs associated with automated screening concluded that similar costs to manual screening could be achieved only if 60,000 samples per year were processed by the AutoPap Primary Screening System (now BD FocalPoint GS Imaging System) with a 30% NFR rate.…”
Section: Productivity and Cost-effectivenessmentioning
confidence: 98%
See 1 more Smart Citation
“…14 Studies published since, which have evaluated the cost and productivity implications associated with using the ThinPrep Imaging System and BD FocalPoint GS Imaging system, have suggested that automation results in both increased productivity and increased costs. In all studies the authors found that automation resulted in at least a 50% 25,26,29 increase in productivity, with the biggest increase reported being 56%. 32 A study based in Italy which estimated the costs associated with automated screening concluded that similar costs to manual screening could be achieved only if 60,000 samples per year were processed by the AutoPap Primary Screening System (now BD FocalPoint GS Imaging System) with a 30% NFR rate.…”
Section: Productivity and Cost-effectivenessmentioning
confidence: 98%
“…In the manual-only arm the FMR is by definition equivalent to the MR. Comparison between manual and automated readings in the paired arm The effect of checking on serial readings is shown in Tables [20][21][22][23][24][25][26]. When the MR1 was compared with the FMR, a large proportion of low grades (29.5%) were downgraded to negative.…”
Section: Comparison Between Manual Readings In Manual-only Armmentioning
confidence: 99%
“…The screening time for each slide (including any reviews by the supervisor) and the maximum workloads per cytologist considered in our study, based on those in the international literature [31,32,33,34,35,36,37,38], are shown in table 1. Fully automatic computer-assisted screening reduced the time of conventional cytology by 64% and of LBC by 40%.…”
Section: Resultsmentioning
confidence: 99%
“…A Danish laboratory in Odense (also having used PAPNET in the past century) remarked that in all 10 false-negative cases, the abnormal cells had been identified by the scanner, but misinterpreted by the CT [12]. These findings stress the importance of carefulness in the interpretation of the marked fields.…”
Section: Discussionmentioning
confidence: 99%